The Application and Relevancy of Rainfall-Runoff-Inundation (RRI) Model in Indonesia - M. Faisi Ikhwali; Budi Azhari; Alfin Khari; Suardi Nur; Abd Mujahid Hamdan; Kingkao Prommacot (Elkawnie, 2023)
Abstract: Indonesia has a very large number of watersheds and has a very diverse size. Damage to several watersheds in Indonesia has also occurred and often results in catastrophic floods and droughts that threaten people. The presence of the RRI Model with its capabilities will help contribute to watershed management in order to solve water resource problems. The RRI model is a two-dimensional (2D) model capable of simulating runoff, rainfall, and flood inundation simultaneously. The use of this model in Indonesia has reached 13 times which was compiled based on the number of publications on the application of the RRI model. All of these publications have passed peer-reviewed papers from both journals and conference papers. Applications have been made in several places including the Solo watershed, the Upper Citarum watershed, the Batanghari watershed, and the upstream Brantas watershed. Given the increasing number of problematic watersheds in Indonesia, the use of this model has the prospect and relevancy of being carried out in other watersheds. However, until now, researchers have had challenges in building hydrological models because of the constraints on the availability of climatological and hydrological data in the watershed. Therefore, in addition to improving the data measuring infrastructure in the field, remote sensing techniques are also needed in an effort to generate targeted watershed information. In fact, the effort to utilize remote sensing in generating unmeasurable data in the field has been successfully conducted in several studies.Abstrak: Indonesia memliki jumlah DAS yang sangat banyak dan memiliki ukuran yang sangat beragam. Kerusakan beberapa DAS di Indonesia juga telah terjadi dan sering berakibat bencana banjir dan kekeringan yang mengancam penduduk setempat. Kehadiran Model RRI dengan kemampuannya akan membantu berkontribusi dalam memajemen DAS ataupun dalam usaha untuk menyelesaikan permasalahan sumberdaya air. Model RRI adalah suatu model dua dimensi (2D) yang memiliki kemampuan untuk mensimulasikan limpasan curah hujan dan genangan banjir secara simultan. Penggunaan model RRI ini di Indonesia telah mencapai 13 kali, yang tercatat berdasarkan jumlah publikasi yang terkait dengan aplikasi model RRI. Semua publikasi tersebut telah melewati peer-review baik dari jurnal maupun dari konferensi. Aplikasi telah dilakukan dibeberapa tempat termasuk DAS Solo, DAS Citarum, DAS Batanghari, dan DAS Brantas. Mengingat jumlah DAS yang bermasalah di Indonesia semakin meningkat, maka penggunaan model ini memiliki prospek untuk dilakukan di DAS lain. Namun sampai saat ini, para peneliti memiliki tantangan dalam membangun permodelan hidrologi karena terkendala pada ketersediaan data klimatologi dan hidrologi di dalam DAS. Oleh karena itu, selain peningkatan infrastruktur pengukur data dilapangan dan teknik pengindraan jauh juga diperlukan dalam usaha menyediakan informasi DAS yang ditargetkan. Usaha penggunaan teknik pengindraan jauh dalam menyediakan data yang tidak terukur dilapangan telah sukses dan terbukti dilakukan di beberapa studi.